Stability of multipliers on Banach algebras - Takeshi Miura; Go Hirasawa; Sin-Ei Takahasi (International Journal of Mathematics and Mathematical Sciences)
Suppose A is a Banach algebra without order. We show that an approximate multiplier T:A→A is an exact multiplier. We also consider an approximate multiplier T on a Banach algebra which need not be without order. If, in addition, T is approximately additive, then we prove the Hyers-Ulam-Rassias stability of T.